ANALISIS IMPLEMENTASI PELAYANAN VOLUNTARY COUNSELING AND TESTING (VCT) DI PUSKESMAS SIDOMULYO RAWAT INAP KOTA PEKANBARU - Ratna Juwita; Zurni Seprina; Zakiah - (Universitas Prima Indonesia, 2022)
Voluntary Counseling and Testing (VCT) is a process of voluntary counseling and HIV testing at the initiative of the individual concerned. The number of VCT visits at the Sidomulyo Inpatient Health Center has decreased from 2018 which was 35.5%, in 2019 as many as 18.5% and in 2020 11.2%. The purpose of this study was to analyze the implementation of Voluntary Counseling and Testing (VCT) services at UPTD Puskesmas Sidomulyo Inpatient Pekanbaru City. This study used a qualitative research design based on the input components and the VCT service process, with the number of informants was 13 people. The results of the study indicate that human resources for VCT services at the Sidomulyo Inpatient Health Center already have a team, consisting of doctors, paramedics, administrative officers and laboratory officers. However they have other main tasks that must be carried out at the same time. The impact of having multiple tasks makes VCT services less than optimal. Officers in outreach to inspection targets in the field are still lacking where in this outreach requires collaboration with other sectors such as NGOs. The VCT service infrastructure is sufficient, although not up to standard. The VCT service method is in accordance with the SOP/guidelines/technical instructions. The VCT service program at the Sidomulyo Inpatient Health Center has not been going well. This is due to the dual duties of the VCT officer. It is hoped that VCT officers can arrange VCT schedules so that they do not clash with other tasks. Increase cross-sectoral cooperation in targeting. Keywords: implementasi; Voluntary Counselling and Testing (VCT).